LITERASI MANAJEMEN KEUANGAN SEDERHANA PADA UMKM KELURAHAN PATAM LESTARI - Ompusunggu, Hermaya; Husda, Anggun Permata; Rustam, Triana Ananda (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2023)
The presence of financial technology (fintech) in Indonesia helps micro, small and medium enterprises (MSMEs) in developing their businesses. Increased access to the world of banking has made MSME business easier. However, the limited ability of MSME players to apply fintech hinders its spread.